Marigold, Tagetes patula, a Trap Plant for Western Flower Thrips, Frankliniella occidentalis, in Ornamental Bedding Plants Under Controlled Greenhouse Conditions - Cheryl Frank Sullivan; Bruce L. Parker; Margaret Skinner (Insects)
Western flower thrips (WFT), Frankliniella occidentalis (Pergande) [Thysanoptera: Thripidae], is a destructive pest of greenhouse ornamentals. Flowering yellow marigolds, Tagetes patula (L.) [Asterales: Asteraceae], have been shown to be attractive to WFT, implicating their suitability as a trap plant. However, functionality may vary in part due to crop variety, the growth stage of the crop in which the marigold trap plant is deployed and whether or not the crop plants have flowers present. The attractiveness of yellow marigolds was tested within several varieties of mature, flowering ornamental bedding plants that were flowering or had their flowers removed: Calibrachoa spp. Petunia spp. Verbena spp., Osteospermum spp., Impatiens haekeri and other marigolds. Trials were conducted in cages under controlled greenhouse conditions for six weeks. The effectiveness of orange vs. yellow marigolds as a trap plant was also assessed. The results showed that WFT were attracted to flowering marigolds and, over time, were present in greater numbers on these than crop plants for all crop species and varieties tested at varying levels of significance. Yellow marigold trap plants were the least effective when deployed within other marigold varieties. In crops with flowers, it took up to five weeks for the number of WFT on trap plants to surpass numbers on crop plants. In contrast, in crop varieties with their flowers removed, trap plants attracted WFT earlier, within one to two weeks, and harbored them in greater numbers over time. Orange, flowering marigolds were a less effective trap plant compared to yellow marigolds. These results confirm that flowering yellow marigolds are attractive to WFT and have potential as a trap plant in greenhouse ornamentals, particularly when crop plants do not have flowers.